PKM Peningkatan Kapasitas Guru Melalui Media Pembelajaran Mind Mapping di Sekolah Yayasan Kemala Bhayangkari - Nur Rahmah; Andi Sukainah; Indrayani; Dewi Puspitasari; Andi Muhammad Akram Mukhlis (Sakura Digital Nusantara, 2023)
The demand for education in the 4.0 era requires that the learning process be able to implement a digital-based learning. System. Strategies in teaching are needed to improve student learning outcomes, one strategy that can be used is the mind mapping method. Through the mind mapping method, students will quickly understand the learning material so that the learning process can be carried out effectively and meet the learning objectives. The aim of this service activity is to improve the ability of Bhayangkari Makassar Middle School teachers in increasing understanding and application of mind mapping learning media. With this training, it is hoped that Kemala Bhayangkari Middle School teachers will be able to apply mind mapping in the learning process. This activity is carried out based on three stages, namely: (1) preparation, (2) activity stage and (3) evaluation stage. The results obtained by the PKM team of the PTP Study Program, Faculty of Engineering, were that the Kemala Bhayangkara Middle School teachers were able to apply the Mind Mapping learning method. This can be seen from the participants' enthusiasm in understanding and applying mind mapping. This training will also provide benefits especially for students in terms of learning methods. Improving the quality of learning will be better and not always conventional.